Thea Stilton, big trouble in the Big Apple - Stilton, Thea.; Stilton, Geronimo; Battan, Alessandro, 1974-; Clement, Emily (New York : Scholastic, 2011)
"The Thea Sisters travel to New York to cheer for Nicky as she runs the Big Apple Marathon. While there, they visit Pamela's family and have a delicious dinner at the family's pizzeria. But when someone threatens to burn the restaurant down, can the Thea Sisters catch the troublemaker and solve the mystery?"--P. [4] of cover.
At head of title: Geronimo Stilton.
"Original title: Grosso guaio a New York"--T.p. verso.
RL3.
007-010.
Keywords: Stilton, Thea -- Juvenile fiction; Mice -- Juvenile fiction; Journalists -- Juvenile fiction; Schools -- Juvenile fiction; Mice -- Fiction; Journalists -- Fiction; Schools -- Fiction; Teachers -- Fiction; New York (N.Y.) -- Juvenile fiction; New York (N.Y.) -- Fiction; Mystery and detective stories